Study the psychological unit and its relationship to the achievement of a 200 meter freestyle event for junior swimmers aged (13-14) years - Khalaf, Othman Mahjoub; Hani, Ahmed Thare; Jasem, Zeena Khaled (International Journal of Psychosocial Rehabilitation, 2020)
The swimmer is running the race alone and far from his teammates or coaches because the competition is in the water medium and thus this may constitute a kind of psychological unity or a feeling of it. Therefore the researchers decided to study this problem because the importance of research lies in studying the level of psychological unity of young swimmers and how it relates to the level of achievement The activity of 200 meters freestyle swimming The research aims to identify the relationship between the psychological unit and the achievement of the effectiveness of the 200 meters freestyle swimming for the junior group through the use of the psychological unit measure, and the researchers used the descriptive approach in order to suit the nature of the problem as the research procedures were carried out on a sample chosen by the intentional method and its strength (22 A junior swimmer from the Army Free Swimming Club, knowing that the pilot experiment was conducted on (3) swimmers outside the main sample sample, and after statistical treatments, the results showed a negative correlation between the psychological unit and the achievement of the 200 meter freestyle activity for the Junior Club swimmers. On the basis of this, the researchers recommended training in psychological skills at an early age, as this has an effect on mathematical achievement and to carry out multiple studies on Psychological acuity in the sports field in general and other types of swimming in particular.